Isolated diastolic hypertension as defined by the 2017 American College of Cardiology/American Heart Association blood pressure guideline and incident cardiovascular events in Chinese - Wu, Shouling; Ji, Chunpeng; Shi, Jihong; Chen, Shuohua; Huang, Zhe; Jonas, Jost B. (Journal of hypertension, 2021)
Objective: - The new arterial hypertension guidelines by the 2017 American College of Cardiology (ACC)/American Heart Association (AHA) changed the definition of isolated diastolic hypertension (IDH). We assessed and compared in a Chinese population the IDH prevalence, newly defined by the 2017 ACC/AHA guidelines versus the former definition by the Joint National Committee 7 (JNC7) criteria, and examined longitudinal associations of IDH with cardiovascular disease (CVD) outcomes. - Methods: - The prospective community-based Kailuan Study included participants aged 18-98 years who underwent a detailed medical examination at baseline in 2006/2007 and who were biennially re-examined till 2017. History of antihypertensive medication at baseline was an exclusion criterion. - Results: - The study population consisted of 87 346 individuals (mean age: 50.9 years; range: 18-98 years). Prevalence of IDH was 7.79% [95% confidence interval (CI): 7.62, 7.97] by JNC7 guidelines and 24.72% (95% CI: 24.43, 25.01) by 2017 ACC/AHA criteria [difference: 19.93% (95% CI: 16.81, 17.04)]. Applying the 2017 ACC/AHA guidelines, the prevalence of IDH-recommended antihypertensive therapy was 7.73% (95% CI: 7.55, 7.90). In multivariable analysis, IDH by JNC7 criteria was significantly associated with incident myocardial infarction [n = 93 events; hazard ratio: 1.30 (95 CI: 1.02, 1.66)], cerebral hemorrhage [n = 73 events; hazard ratio: 1.79 (95% CI: 1.35, 2.38)], and total CVD [n = 373 events; hazard ratio: 1.15 (95% CI: 1.02, 1.30)], when compared with normotension. IDH based on 2017 ACC/AHA guidelines was associated with incident cerebral hemorrhage [n = 129 events; hazard ratio: 1.47 (95% CI: 1.12, 1.94)] and total CVD [n = 828 events; hazard ratio: 1.13 (95% CI: 1.02, 1.26)]. - Conclusion: - In this adult Chinese community, 2017 ACC/AHA-defined IDH was associated with the incidence of cerebral hemorrhage and total CVD, and as compared with JNC7-defined IDH, it was more prevalent.
Gesehen am 13.07.2021